Breaking Down the Barrier: The Role of Cervical Infection and Inflammation in Preterm Birth - Tantengco, Ourlad Alzeus G.; Menon, Ramkumar (Frontiers in Global Women's Health, 2022)
Approximately 40% of cases of spontaneous preterm birth (sPTB) are associated with ascending intrauterine infections. The cervix serves as a physical and immunological gatekeeper, preventing the ascent of microorganisms from the vagina to the amniotic cavity. The cervix undergoes remodeling during pregnancy. It remains firm and closed from the start until the late third trimester of pregnancy and then dilates and effaces to accommodate the passage of the fetus during delivery. Remodeling proceeds appropriately and timely to maintain the pregnancy until term delivery. However, risk factors, such as acute and chronic infection and local inflammation in the cervix, may compromise cervical integrity and result in premature remodeling, predisposing to sPTB. Previous clinical studies have established bacterial (i.e., chlamydia, gonorrhea, mycoplasma, etc.) and viral infections (i.e., herpesviruses and human papillomaviruses) as risk factors of PTB. However, the exact mechanism leading to PTB is still unknown. This review focuses on: (1) the epidemiology of cervical infections in pregnant patients; (2) cellular mechanisms that may explain the association of cervical infections to premature cervical ripening and PTB; (3) endogenous defense mechanisms of the cervix that protect the uterine cavity from infection and inflammation; and (4) potential inflammatory biomarkers associated with cervical infection that can serve as prognostic markers for premature cervical ripening and PTB. This review will provide mechanistic insights on cervical functions to assist in managing cervical infections during pregnancy.